Benefits and Barriers to Increasing Regional Anesthesia in Resource-Limited Settings - Dohlman, Lena Ebba; Kwikiriza, Andrew; Ehie, Odinakachukwu (Dovepress, 2020)
Abstract: Safe and accessible surgical and anesthetic care is critically limited for over half of the world’s population, particularly in Sub-Saharan African and Southeast Asian countries. Increasing the use of regional anesthesia in these areas has potential benefits regarding access, safety, and cost-effectiveness. Perioperative anesthesia-related mortality is significantly higher in resource-limited countries and every effort should be made to encourage the use of anesthetic techniques in these countries that are safest under the present conditions. Studies from Sub-Saharan Africa, although limited in number, have shown a lower risk of death with regional compared to general anesthesia. Regional anesthesia has the further benefit of decreasing the risk of COVID-19 spread to healthcare providers by avoiding the aerosol-generating procedures that occur during general anesthesia. Neuraxial regional anesthesia is relatively easy to teach and perform and is considered the anesthetic of choice for surgeries below the umbilicus in resource-limited settings due to its safety, efficacy, and low cost. Although regional anesthesia has multiple potential advantages, education and training of anesthetic providers in low-and-middle-income countries (LMIC) are a significant barrier to growth. Anesthesia professionals, especially in Sub-Saharan Africa, are often poorly supported and undervalued, and recruitment and retention of adequate numbers of trained practitioners are a continuing problem. Greater use of regional anesthesia could be one way to safely increase anesthesia access and simultaneously create value and enthusiasm for the field. Deficits in anesthesia infrastructure, equipment, and drugs also limit anesthesia capacity in low-and middle-income countries. Ultrasound-guided regional anesthesia may be helpful in improving access to safe and reliable anesthesia in low-resource countries as it continues to become more user-friendly, durable, and affordable. Keywords: low-resource countries, developing countries, regional anesthesia, ultrasound-guided nerve blocks, anesthesia safety
Keywords: Developing countries; Low-resource countries; Regional anesthesia; Ultrasoundguided nerve blocks; Anesthesia safety